Nano-structuring, surface and bulk modification with a focused helium ion beam - Fox, Daniel; Chen, Yanhui; Faulkner, Colm C.; Zhang, Hongzhou (Beilstein Journal of Nanotechnology, 2012)
We investigate the ability of a focused helium ion beam to selectively modify and mill materials. The sub nanometer probe size of the helium ion microscope used provides lateral control not previously available for helium ion irradiation experiments. At high incidence angles the helium ions were found to remove surface material from a silicon lamella leaving the subsurface structure intact for further analysis. Surface roughness and contaminants were both reduced by the irradiation process. Fabrication is also realized with a high level of patterning acuity. Implantation of helium beneath the surface of the sample is visualized in cross section allowing direct observation of the extended effects of high dose irradiation. The effect of the irradiation on the crystal structure of the material is presented. Applications of the sample modification process are presented and further prospects discussed.
Keywords: EELS; EFTEM; helium ion microscopy; nanofabrication; TEM

(untitled) - Na, H.-J.; Lee, J.-W.; Lee, W.-K.; Lim, J.-H.; Park, H.-G.; Kim, B.-Y.; Hwang, J.-Y.; Han, J.-M.; Seo, D.-S. (Opt. Lett., 2010)

(untitled) - Colli, A.; Fasoli, A.; Ronning, C.; Pisana, S.; Piscanec, S.; Ferrari, A. C. (Nano Lett., 2008)

(untitled) - Panigrahy, B.; Aslam, M.; Bahadur, D. (Appl. Phys. Lett., 2011)

(untitled) - Wong, K. K. H.; Hutter, J. L.; Zinke-Allmang, M.; Wan, W. (Eur. Polym. J., 2009)

(untitled) - Raffa, V.; Vittorio, O.; Pensabene, V.; Menciassi, A.; Dario, P. (IEEE Trans. NanoBiosci., 2008)

(untitled) - Wirth, R. (Chem. Geol., 2009)

(untitled) - Kiener, D.; Motz, C.; Rester, M.; Jenko, M.; Dehm, G. (Mater. Sci. Eng., A, 2007)

(untitled) - Genet, C.; Ebbesen, T. W. (Nature, 2007)

Proceedings of 11th International Conference on Electronic Packaging Technology & High Density Packaging (ICEPT-HDP 2010) - Yuan, C.; Xiaowen, Z. (Focused ion beam technology and application in failure analysis, Xi'an, China, 16.8.2010-19.8.2010, 2010)

(untitled) - Ward, B. W.; Notte, J. A.; Economou, N. P. (J. Vac. Sci. Technol., B, 2006)

(untitled) - Lemme, M. C.; Bell, D. C.; Williams, J. R.; Stern, L. A.; Baugher, B. W. H.; Jarillo-Herrero, P.; Marcus, C. M. (ACS Nano, 2009)

(untitled) - Bell, D. C.; Lemme, M. C.; Stern, L. A.; Williams, J. R.; Marcus, C. M. (Nanotechnology, 2009)

16th International Conference on Solid-State Sensors, Actuators and Microsystems Conference (TRANSDUCERS 2011) - Annamalai, M.; Mathew, S.; Viswanathan, V.; Fang, C.; Pickard, D. S.; Palaniapan, M. (Design, fabrication and Helium Ion Microscope patterning of suspended nanomechanical graphene structures for NEMS applications, Beijing, China, 5.6.2011-9.6.2011, 2011)

(untitled) - Chen, P.; van Veldhoven, E.; Sanford, C. A.; Salemink, H. W. M.; Maas, D. J.; Smith, D. A.; Rack, P. D.; Alkemade, P. F. A. (Nanotechnology, 2010)

(untitled) - van Veldhoven, E.; Sidorkin, V.; Chen, P.; Alkemade, P.; van der Drift, E.; Salemink, H.; Zandbergen, H. W.; Maas, D. (Microsc. Microanal., 2010)

Nanofabrication: Techniques and Principles - Alkemade, P. F. A.; van Veldhoven, E. (Deposition, Milling, and Etching with a Focused Helium Ion Beam, 2011)

(untitled) - Livengood, R.; Tan, S.; Greenzweig, Y.; Notte, J.; McVey, S. (J. Vac. Sci. Technol., B, 2009)

(untitled) - Ebihara, A.; Tokitani, M.; Tokunaga, K.; Fujiwara, T.; Sagara, A.; Yoshida, N. (J. Nucl. Mater., 2007)

(untitled) - Pearson, A. J.; Boden, S. A.; Bagnall, D. M.; Lidzey, D. G.; Rodenburg, C. (Nano Lett., 2011)

(untitled) - Jepson, M. A. E.; Inkson, B. J.; Liu, X.; Scipioni, L.; Rodenburg, C. (EPL, 2009)

(untitled) - Bazou, D.; Behan, G.; Reid, C.; Boland, J. J.; Zhang, H. Z. (J. Microsc. (Oxford, U. K.), 2011)

(untitled) - Lee, C. W.; Ikematsu, Y.; Shindo, D. (J. Electron Microsc., 2002)

(untitled) - Giannuzzi, L. A.; Geurts, R.; Ringnalda, J. (Microsc. Microanal., 2005)

Electron Energy-Loss Spectroscopy in the Electron Microscope - Egerton, R. F. (Plenum Publishing Corporation, 1996)

(untitled) - Siegele, R.; Weatherly, G. C.; Haugen, H. K.; Lockwood, D. J.; Howe, L. M. (Appl. Phys. Lett., 1995)

Stopping and range of ions in matter - Ziegler, J. F.; Biersack, J. P.; Ziegler, M. D. (Lulu Press, 2008)

(untitled) - Yan, Y.; Page, M.; Wang, T. H.; Al-Jassim, M. M.; Branz, H. M.; Wang, Q. (Appl. Phys. Lett., 2006)

(untitled) - Yang, J.; Ferranti, D. C.; Stern, L. A.; Sanford, C. A.; Huang, J.; Ren, Z.; Qin, L.-C.; Hall, A. R. (Nanotechnology, 2011)

(untitled) - Schaffer, M.; Schaffer, B.; Ramasse, Q.; Falke, M.; Abou-Ras, D.; Schmidt, S.; Caballero, R.; Marquardt, K. (Microsc. Microanal., 2011)

(untitled) - Li, N.; Fu, E. G.; Wang, H.; Carter, J. J.; Shao, L.; Maloy, S. A.; Misra, A.; Zhang, X. (J. Nucl. Mater., 2009)

(untitled) - Sundararajan, J. A.; Zhang, D. T.; Qiang, Y.; Jiang, W.; McCloy, J. S. (J. Appl. Phys., 2011)

(untitled) - Langford, R. M.; Clinton, C. (Micron, 2004)

jems opening page sept 21 2004